(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
This study is aimed at analysing integrated production - inventory policies for deteriorating items in supply chain when demand of product is subject to increase with time. The model assumes partial backlogging, imperfect production process and multiple deliveries. The elapsed time until the production process shifts is assumed to be exponentially distributed. It is observed that the joint decision lowers the total cost compared with an independent decisions made by the manufacturer and the retailer with the help of numerical data. The sensitivity analysis is carried out to study the variation in the decision variables and the total integrated cost.